2018
DOI: 10.1007/s10006-018-0685-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic study of mandibular third molars: evaluation of the position and root anatomy in Brazilian population

Abstract: The present study showed that the most prevalent mandibular third molar type in Brazilian patients was the IA and mesioangular position, with simple root anatomy. The result of this study can assist oral surgeons to better plan and assess the level of difficulty of surgical removal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
3
6
0
4
Order By: Relevance
“…In contrast, our findings corroborated a study conducted among Brazilian population on anatomy of mandibular third molars [16]. Findings of that study revealed the most common pattern was two roots (98.3%), Further, the same study reported conical simple type (88.9%), with absence of laceration (89.2%), divergence (84%), and fusion (80%) [16]. However, in our study, occurrence of fusion was only 22.3% and divergence was as low as 4.2%.…”
Section: Pattern Of Root Morphology and Its Association With Surgical Processessupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, our findings corroborated a study conducted among Brazilian population on anatomy of mandibular third molars [16]. Findings of that study revealed the most common pattern was two roots (98.3%), Further, the same study reported conical simple type (88.9%), with absence of laceration (89.2%), divergence (84%), and fusion (80%) [16]. However, in our study, occurrence of fusion was only 22.3% and divergence was as low as 4.2%.…”
Section: Pattern Of Root Morphology and Its Association With Surgical Processessupporting
confidence: 91%
“…In our study, only 0.8% was three-rooted and four roots were not reported. In contrast, our findings corroborated a study conducted among Brazilian population on anatomy of mandibular third molars [16]. Findings of that study revealed the most common pattern was two roots (98.3%), Further, the same study reported conical simple type (88.9%), with absence of laceration (89.2%), divergence (84%), and fusion (80%) [16].…”
Section: Pattern Of Root Morphology and Its Association With Surgical Processessupporting
confidence: 90%
“…However, in reviewing most oral and maxillofacial surgery recommendations and references, there is inadequate information about the best method of extraction of this ball attached to the root safely and the only advice given is to be cautious during extraction. 4 In Saudi population in Sakaka, Aljouf, the frequency of hypercementosis is low (4.8%) as reported by Patil et al, in 2018: whereas, in Almadinah Almunawwarah, hypercementosis may be a relatively common finding, and its influence on the treatment of teeth affected by this alteration should be realised by the dentists. 5 Therefore, the purpose of the current report is to introduce this case of hypercementosis, review and update the recommended surgical techniques used for extraction, and to explore more avenues on the surgical treatment of hypercementosed teeth with the least complication.…”
Section: Introductionmentioning
confidence: 91%
“…The calcified SHL and an elongated styloid process can be radiographically identified, and although the panoramic oral X-ray is easily assessed, it is prone to frequent errors [18]. When simple X-ray is not conclusive, 3D CT is the method of choice for confirming ES diagnosis [19, 20].…”
Section: Discussionmentioning
confidence: 99%